BULLYING, VICTIMIZATION, AND REJECTION SENSITIVITY IN ADOLESCENTS: MEDIATING ROLE OF SELF-REGULATION - Sameera Shafiq; Sidra Batool (Journal of Postgraduate Medical Institute, 2021)
Objective: To explore the mediating role of self-regulation in bullying, victimization as related with rejection sensitivity among adolescents. Methodology: This cross-sectional research was conducted at the Department of Psychology, University of Gujrat after taking approval from Advanced Studies and Research Board. In first phase, Self-Regulation Questionnaire (SRQ) and Rejection Sensitivity Questionnaire (RSQ) were translated into Urdu language by forward-backward translation method after taking permission from their respective authors. For pilot-testing, these scales were administered on 130 students and scales were found to be reliable with a=0.83 and a=0.85 respectively. In second phase, Urdu version of Adolescent Peer Relations Instrument (ARRI) by Parada, SRQ, and RSQ were administered to a sample of 608 college students. Stratified Random Sampling technique was use to collect the data. The data was analyzed in AMOS-21. Results: The study reported male as 330, and female as 278, age range between 16 to 19 years with mean of 17.60±0.83 years. The model fit indices of chi-square/df =2.2 (p<0.001), Goodness of fit (GFI)=0.94, Adjusted goodness of fit (AGFI)=0.91, Comparative fit index (CFI)=0.904, Incremental fit index (IFI)=0.906, Tucker Lewis index (TLI)= 0.88 and Root Mean Square Error of Approximation (RMSEA)=0.046 were in the acceptable limits. Structure Equation Model in AMOS-21 showed significant mediating role of self-regulation with bullying, victimization and rejection sensitivity among adolescents. Conclusion: Self-regulation has fully and significantly mediated the association of both bullying and victimization with the level of sensitivity for rejection in adolescents.